Emergence of a thrombospondin superfamily at the origin of metazoans - Shoemark, Deborah; Ziegler, Bérénice; Watanabe, Hiroshi; Strompen, Jennifer; Tucker, Richard P.; Özbek, Suat; Adams, Josephine C. (Molecular biology and evolution, 2019)
Extracellular matrix (ECM) is considered central to the evolution of metazoan multicellularity; however, the repertoire of ECM proteins in nonbilaterians remains unclear. Thrombospondins (TSPs) are known to be well conserved from cnidarians to vertebrates, yet to date have been considered a unique family, principally studied for matricellular functions in vertebrates. Through searches utilizing the highly conserved C-terminal region of TSPs, we identify undisclosed new families of TSP-related proteins in metazoans, designated mega-TSP, sushi-TSP, and poriferan-TSP, each with a distinctive phylogenetic distribution. These proteins share the TSP C-terminal region domain architecture, as determined by domain composition and analysis of molecular models against known structures. Mega-TSPs, the only form identified in ctenophores, are typically >2,700 aa and are also characterized by N-terminal leucine-rich repeats and central cadherin/immunoglobulin domains. In cnidarians, which have a well-defined ECM, Mega-TSP was expressed throughout embryogenesis in Nematostella vectensis, with dynamic endodermal expression in larvae and primary polyps and widespread ectodermal expression in adult Nematostella vectensis and Hydra magnipapillata polyps. Hydra Mega-TSP was also expressed during regeneration and siRNA-silencing of Mega-TSP in Hydra caused specific blockade of head regeneration. Molecular phylogenetic analyses based on the conserved TSP C-terminal region identified each of the TSP-related groups to form clades distinct from the canonical TSPs. We discuss models for the evolution of the newly defined TSP superfamily by gene duplications, radiation, and gene losses from a debut in the last metazoan common ancestor. Together, the data provide new insight into the evolution of ECM and tissue organization in metazoans.
Gesehen am 26.09.2019